Grain Sorghum Water Use Efficiency and Yield Are Impacted by Tillage Management Systems, Stubble Height, and Crop Rotation. Issue 1 (10th March 2017) - Darapuneni, Murali K.; Angadi, Sangamesh V.; Begna, Sultan; Lauriault, Leonard M.; Umesh, M.R.; Kirksey, Rex; Marsalis, Mark
Abstract : Core Ideas: Tillage, stubble management, and crop rotation are important management decisions for maximizing productivity and profitability in semi‐arid environments. Under poor rainfall distribution conditions of sandy loam, most positive effects of tillage‐stubble management were partially moderated by a significant rotation × tillage‐stubble interaction. Under above‐average rainfall conditions of clay loam, yield characteristics were influenced by neither rotation nor tillage‐stubble management. Conservation tillage combined with stubble management resulted in greater WUE than conventional tillage with no residue management at one out of two locations. Successful crop production in semiarid environments of the Southern High Plains depends on critical management practices such as tillage, stubble management, and crop rotation that maximize the use efficiency of limited resources. An experiment was conducted at two locations in 2010, after the first year of rainfed crop rotation (continuous grain sorghum [ Sorghum bicolor (L.) Moench] or cowpea [ Vigna unquiculata (L.) Walp.]–sorghum), tillage (conventional, strip‐till, or no‐till) and stubble height (short and tall in strip‐ or no‐till) had been imposed, to evaluate the effects of these management factors on early growth, yield characteristics, and water use efficiency of grain sorghum. Based on the results, the influence of tillage‐stubble management on yield and water use characteristics varied with soil type and seasonal rainfall pattern. Under poor rainfall distribution conditions of Tucumcari sandy loam, the most positive effects of tillage‐stubble management were partially moderated by a significant rotation × tillage‐stubble interaction. Under above‐average rainfall conditions at the Clovis site, which has clay loam soils, yield characteristics were influenced by neither rotation nor tillage‐stubble management. However, at Clovis, conservation tillage (no‐till and strip‐till) in combination with stubble management (short and tall) resulted in greater WUE than conventional tillage with no residue management ( P < 0.05). A long‐term study is needed to make recommendations on the adoption of suitable conservation tillage and stubble management strategies in this region; however, the results of this work are encouraging and indicate potential benefits of conservation tillage and stubble management in semiarid environments.